Silver Ion Mediated In Situ Synthesis of Mixed Diaryl Sulfides from Diaryl Disulfides - Gogoi, Prasanta; Gogoi, Sandhya R.; Kalita, Mukul; Barman, Pranjit (Synlett, 2013)
The AgNO3-mediated in situ scission of aromatic disulfides in the presence of electron-rich aromatic compounds results in the efficient synthesis of diaryl sulfides. Key features of this new methodology are high yields of aromatic and heteroaromatic sulfides, mild reaction conditions, simplicity, simple workup, and avoiding foul-smelling reactants like thiols.
Keywords: in situ synthesis; disulfide; sulfenylation; metal-mediated